EXPERIMENTAL STUDY OF THE SNOW REMOVAL PROCESS BY HELICAL BLADE OF THE MILLING FEEDER - Moldakhanov, Bekbolat; Doudkin, Mikhail; Kim, Alina; Rogovsky, Valery; Andryukhov , Nikita (Journal of Applied Engineering Science, 2022)
The article presents the process effectiveness evaluation of the throwing snow mass from the face into the operating area of the snowplow rotor-thrower by a milling feeder, when using a paddle type intensifier. During the operation of the milling-rotor snowplow, an operational problem sometimes arises, arising from an incorrectly set slope (angle of elevation) of the helical line of the milling feeder, due to which snow is thrown forward by it along the snowplow, forming an additional amount of snow for processing, which increases the overall energy costs for the development of snow and the movement of the machine in the snow massif and at the same time reduces the performance of the snowplow [1, 2]. The area of rational values of the design and operating parameters of the milling feeder and the bladed intensifier of the snowplow has been calculated. The process of efficiency increase of the milling-rotary snowplow (MRS) and its performance by adjusting the helix angle α and installing a bladed intensifier reducing the power of the working process will make it possible to perform work on clearing snow and ice formations using reduced number of machines, moreover in much less time. A more massive supply of snow mass to the blades of the rotor-thrower due to the use of an intensifier will lead to a decrease in the total energy costs for the snowplow working process. Therefore, by increase the working equipment efficiency of a MRS with the energy intensity decrease of snow development by selecting rational parameters for its design and workflow is the simplest and most effective way to rationally organize the workflow and improve machines of this type of snowplow.